INVESTIGATION OF ROTARY SPEED INFLUENCE ON STRUCTURE AND CHARACTERISTICS OF ZINC ALLOY ZnAl4Cu3 AT SPIN CASTING IN SILICONE MOULDS - M. Bajchichak; M. Beznak; A. S. Chaus (Литьë и металлургия)
Influence of the mould rotary speed on the structure and characteristics of zinc alloy ZnAl4Cu3 at centrifugal casting in silicone moulds using technology TEKCAST is investigated.